Cooperative mechanisms of oxide ion conduction in tellurites with secondary bond interactions and Grotthuss-like processes - Zhenyu Zhu; Guanqun Cai; Yuxiang Feng; Juping Xu; Shengqi Chu; Pengfei An; Jianrong Zeng; Wen Yin; Yu Gu; Xiaojun Kuang; Junliang Sun (Nature Communications)
Abstract Oxide-ion conducting materials are gaining considerable attention in various applications ranging from oxide fuel cells to oxygen permeation membranes. The oxide ion migration mechanisms are the basis for designing oxide-ion conducting materials. Here, enlightened by proton diffusion in hydrogen-bond networks, we report the coordination polyhedra cooperative mechanism with similar Grotthuss process of oxide ion migration in tellurites. Bi2Te2O7 and Bi2Te4O11 were selected due to their abundance of secondary bonds similar to hydrogen bonds and show high oxide ionic conductivity as mixed electronic and ionic conductors. Neutron total scattering experiments with reverse Monte Carlo simulations indicated that the oxide ion migration in those two tellurites is a synergetic effect of mutual transition between Te-O secondary bonds and covalent bonds assisted by Te-O polyhedra rotation. This detailed investigation of the cooperative mechanism with similar Grotthuss process at the atomic scale provides a direction for optimization and discovering oxide ion conducting materials.